Sediment and Contaminant Transport in Surface Waters - Lick, Wilbert (CRC Press, 2009)
Contaminated bottom sediments and their negative impacts on water quality are a major problem in surface waters. Sediment and Contaminant Transport in Surface Waters provides a quantitative understanding of the transport of sediments and hydrophobic contaminants. With an emphasis on fine-grained, cohesive sediments and mixtures of fine-grained and coarse-grained sediments, this book provides detailed descriptions of models for resuspension, erosion, deposition, and transport. Various applications of each model are presented. The text also focuses on flux mechanisms, the effects of finite rates, the impact of large-scale events, and determining parameters from laboratory experiments.